The Benefits of Electronic Health Record (EHR) on Operating Room Efficiency: Literature Review - Juita, Juita; Herawati, Tuti (UIMA Press, 2021)
Background:The Electronic Health Record (EHR) system is a systematic collection of health information based on electronics and integrated with information systems in the hospital network. The use of the EHR system is very important in a comprehensive strategy to improve the quality of health and patient safety, especially in the operating room. Purpose: to find out the benefits of using EHR on operating room efficiency which includes treatment costs, OR efficiency metrics, turn over time, documentation time and nursing quality. Method: This literature review was searched through relevant evidence-based studies usingdatabase at PROQUEST, Science Direct, Scopus, Elsevier from 2017-2021. Results:The EHR system has a cost-saving impact on the average operating room cost of 36-37 dollars per minute and can reduce costs during pre, intra and post surgery. For the FPIR value from the data of 27,403 cases after post-implementation to 9,630 cases, it means that there are no missing patients to enter the operating room, while at the time of delay the FCOTSin pre-implementation of EHR was 1972 cases or (7.20%) and post-implementation 377 cases (3.91%). Meanwhile, the turn over time (TOT) after post implementation showed a significant increase of 53 minutes, p < 0.001. The introduction of the EHR also had an impact on increasing documentation time for nurses from 23% to 35%. In addition, it also provides benefits to the quantity and quality of nursing. Conclusion: The usefulness of the EHR system contributes to increasing the efficiency of the operating room so that it can provide effectiveness in service and quality of care. Nurses are expected to be able to input the EHR system and service agencies can implement these technological developments